Spatial dimensions of illiteracy in Romania, 1992–2011 - Buza, Victoria (Frontiers in Sociology, 2022)
Starting with the chapter approaching the educational characteristics of the three census databases carried out in post-communist Romania (1992, 2002, and 2011), broken down at the local administrative unit level, the article aims to analyze from a geographical perspective the phenomenon of illiteracy. In the collective mindset, this notion is primarily associated with poverty, lack of accessibility to education, and/or lack of interest in school. During the three decades covered by this study, influenced by the change of the communist political regime and the economic instability, the complexity of the spatial dimensions of illiteracy is defined by particular demographic, confessional, and ethnic connections which have experienced various dynamics, but following the general tendency of the peripheralization of the phenomenon. Although the Romanian education system adopted certain Western reforms and implemented certain modern strategies, its quasi-obsolete strategies have persisted or have been aggravated in certain well-defined communities, which have been evolving against the downward trend, betraying a severe educational failure, especially in the south of the Romanian Plain, the south of Dobrogea Region, and in Transylvanian Depression. Therefore, in pursuing the implications of the ethnic and religious heritage, as well as the residential area factor, this research is devoted to the study of the main geographical areas where illiteracy is still present and to its relations with the social and economic environment.